Penyelesaian Wanprestasi oleh Nasabah dalam Akad Murabahah pada Kredit Pemilikan Rumah Syariah di Bank Muamalat Cabang Surabaya - Abigail Shania Azzafira; Sri Maharani (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2022)
In this writing, this study aims to determine the implementation of the murabahah contract on sharia home ownership loans and the settlement of defaults made by customers in the murabahah agreement for sharia home ownership loans at Bank Muamalat Surabaya Branch. The source of this writing data was obtained from interviews with staff of Bank Muamalat Surabaya Branch, legislation, and various literatures. The author uses empirical juridical research methods, namely the type of sociological legal research and can be called field research, namely examining applicable legal provisions and what happens in reality in society. The house is an important basic need for humans for shelter and not a few people buy houses by KPR. In this paper, the implementation of the murabahah contract on home ownership loans is carried out in several stages from the submission stage to the approval of the disbursement of funds. However, in the mortgage financing provided by Bank Muamalat, problems often arise, namely defaults by customers. Settlement of the default is carried out with non-litigation efforts starting with the stage of issuing a warning letter, restructuring, and finally the auction process. In the process of resolving the default, there are still some people who do not understand. Therefore, the author conducted this writing to find out how the process of settlement of mortgage defaults by customers in a murabahah contract at Bank Muamalat Surabaya Branch.